Digital Overload: Exploring The Relationship Between Social Media Usage And Sleep Deprivation - Heetasha Pradhan (Journal of Informatics Education and Research, 2025)
This study investigates the relationship between social media usage and sleep deprivation among adolescents. With the rapid advancement of digital technology and the widespread availability of smartphones, adolescents today are more connected to social media platforms than ever before. This increasing dependence on social media and phones has raised a significant concern regarding its impact on mental, physical help and particularly sleep quality and duration. The data was collected through an online survey, examined, and backed up by secondary resources. The results revealed that most adolescents use social media for entertainment and often engage in late night scrolling, sacrificing essential rest hours, leading to patterns of sleep deprivation. These findings align with existing literature suggesting that increased nighttime social media use contributes to reduced sleep quality and fatigue. In conclusion, this study concludes that excessive social media use significantly disrupts adolescents sleep patterns.